Islamic Economic Ethics in Customer Complaint Handling: Enhancing Customer Satisfaction at BSI - Habibi Habibi; Rika Dwi Ayu Parmitasari; Nasrullah Bin Sapa (Universitas Muhammadiyah Makassar, 2025)
This study aims to explore the strategic implementation of customer complaint handling at BSI KCP Veteran Makassar in maintaining customer satisfaction and to analyze the application of ethics from the perspective of Islamic economic ethics. The research employs a qualitative approach with a case study method, involving six informants: one manager from BSI KCP Veteran Makassar, three BSI employees, and two BSI customers. Data collection was conducted through observations, interviews, and documentation analysis. The findings reveal that BSI KCP Veteran Makassar has implemented a structured approach to handling customer complaints to ensure customer satisfaction. This is achieved through three key strategies: a continuous improvement strategy, an excellent service strategy, and an effective and efficient complaint handling strategy. These strategies are designed to address customer grievances promptly while enhancing overall service quality. Furthermore, the bank integrates ethical principles in handling complaints, aligning with Islamic economic ethics. The ethics applied include honesty, fairness, responsibility, and professionalism, which reflect the core values of tabligh, amanah, fatonah, and siddiq in Islamic business practices. By upholding these ethical principles, BSI KCP Veteran Makassar ensures that customer concerns are resolved transparently and equitably. Ultimately, the implementation of these strategic and ethical approaches not only resolves customer complaints effectively but also fosters customer trust and loyalty. Maintaining high service standards and adhering to Islamic ethical values strengthen the bank's reputation and contribute to long-term customer retention and satisfaction.